Model Pembelajaran Kitab Al-Jurumiyah di Pondok Pesantren - Latipah Harahap; Darwin Zainuddin (Departement of Mathematics Education, 2023)
This article aims to obtain information about the Al-Jurumiyah Book Learning Model at Islamic Boarding Schools. This research is a library research (Library Research). The library method is a suitable method in this study. Because in this case library sources such as books and journals both nationally and internationally will be used to collect various data relating to instilling the values ​​of monotheism in learning Arabic. From the presentation it can be concluded that there are several methods that can be used to convey knowledge from the book Al-Jurumiyah, including: the Al-Qiyasiyah Model (Analogy), the Istiqroniyah Model (Induction), Example Models, Whole Text Models.